Vanishing bone disease of the orbital roof: Now you see it, now you don't. Issue 5 (27th June 2014) - Dharsono, Ferry; van Heerden, Jolandi; Mesbah Ardakani, Nima; Franconi, Catherine; Honeybul, Stephen; Lind, Christopher R.P.; McAuliffe, William
Summary We describe a rare case of vascularised orbital roof and calvarial erosions with an associated venous malformation. In the absence of infection, malignancy, trauma and eosinophillic granuloma, the closest previously described entity is vanishing bone disease. Computed tomography (CT), MRI, catheter angiography and pathology were all important in the diagnostic workup to enable surgical planning for biopsy and reconstruction. Ongoing CT and MRI follow‐up imaging will determine future treatment planning.